THE EFFECT OF LEADERSHIP STYLE AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE IN PAMBOANG DISTRICT OFFICE MAJENE REGENCY - Artiyany, Megawhati (Jurnal Ekonomi Balance, 2018)
This study aims to determine 1) whether leadership style affects the performance of employees at the Pamboang District Office, Majene Regency., 2) to find out whether career development has an effect on employee performance at the Pamboang District Office, Majene Regency and 3) to find out which variable has a more dominant influence. on the work performance of employees at the East Banggae District Office, Majene Regency. This study uses a quantitative approach, with data analysis techniques using SPSS. The study was conducted for 3 months. The results of this study are 1) Leadership Style affects the Performance of Pamboang District Office Employees, Majene Regency, 2) Career development affects the performance of Pamboang District Office Employees Majene Regency and 3) Of the two variables above Leadership Style and Career Development, the Leadership Style variable is more affect employee performance. Because Leadership Style has a higher tcount than the t-value of Career Development